The role of nurses in the treatment of women with breast cancer: a literature review (Research, Society and Development, 2021)
This study aimed to show the assistance given by nurses to women affected by breast cancer. These women are monitored and guided in their treatments by a multidisciplinary oncology team, however, it is the nurse who is directly linked to the patients, providing care and monitoring in daily practice with care in cancerology. It was about the performance of this professional that this study was developed. The methodology used was bibliographical research with literature review, of the narrative type. The search was performed based on queries to the Scielo, Medline (PubMed) and Lilacs (BVS) databases. The survey was carried out with the following descriptors: "Breast neoplasm" AND and OR "breast cancer" AND and OR "Nurse's role" AND and, OR "Oncology". The search totaled 295 studies, applying the criteria of time (2000/2020) and publications in Portuguese, it was refined to 48, of which 34 were selected. patients diagnosed with breast cancer in health care networks, whether in primary, secondary or tertiary care and also in the post-mortem. Thus, the general conclusion is that the nurse is a fundamental part of the nursing team that integrates the multiprofessional, as he/she is responsible for instituting an interaction between the patient diagnosed with breast cancer and her treatment through therapeutic communication, and at the same time, providing nursing care that meets their expectations and needs, providing physical, emotional and spiritual well-being.